Development of Vasoinhibin-Specific Monoclonal Antibodies - Müller, Nils; Robles, Juan Pablo; Zamora, Magdalena; Ebnet, Johannes; Markl-Hahn, Hülya; Martínez de la Escalera, Gonzalo; Clapp, Carmen; Bertsch, Thomas; Triebel, Jakob (Frontiers in Endocrinology, 2021)
Vasoinhibin is a protein hormone with antiangiogenic, antivasodilatatory, and antivasopermeability effects generated by the proteolytic cleavage of prolactin. The discovery of its role in diabetic retinopathy and peripartum cardiomyopathy led to the evaluation of new pharmacological treatments in clinical interventional trials. However, the quantitative evaluation of vasoinhibin in biological samples from patients has not been possible due to the lack of vasoinhibin-specific antibodies. Recently, loop 1 of vasoinhibin was identified to have a different three-dimensional structure compared to PRL, and thus to contain vasoinhibin-specific epitopes. Here, we report the development of two sets of vasoinhibin-specific monoclonal antibodies against two neighboring regions of vasoinhibin loop 1. An experimental sandwich ELISA with two monoclonal anti-vasoinhibin antibodies was developed, which had no cross-reactivity to recombinant human full-length prolactin. The ELISA had a quantitation limit of 100 ng/ml, and intra-assay- and inter-assay coefficients of variation of 12.5 % and 14 %, respectively. The evaluation of 15 human serum samples demonstrated concentrations of below limit of detection (n=3), below limit of quantitation (n=1) and between 0.23 µg/ml (230 ng/ml) to 605 µg/ml (n=12) in the quantifiable range. Despite the high specificity of the monoclonal-monoclonal antibody sandwiches which discriminate vasoinhibin from PRL, there might be cross-reactivities by serum proteins other than vasoinhibin. A fully established vasoinhibin ELISA may support diagnostic and therapeutic measures in vascular diseases.